Synthesis and Surface Properties of Anionic Gemini Surfactants having N‐acylamide and Carboxylate Groups. Issue 4 (11th January 2014) - Zhou, Yan; Cheng, Yun; Han, Chunyu; Lai, Junling; Sui, Lin; Luo, Genxiang
Abstract: A straightforward synthetic strategy to an anionic gemini surfactant having both N ‐acylamide and carboxylate groups in a molecule has been demonstrated. The surface properties of the anionic gemini surfactant, such as CMC (critical micelle concentration), C20 (the concentration required to reduce the surface tension of the solvent by 20 mN / m), γ CMC (the surface tension at the CMC), ∏ CMC (the surface pressure at the CMC), Γ max (the maximum surface excess concentration at the air/aqueous solution interface), A min (the minimum area per surfactant molecule at the air/water interface), and the CMC/C20 ratio (a measure of the tendency to form micelles relative to adsorbtion at the air/water interface), have been studied. The influence of the different concentrations of NaCl on the surface properties of the gemini surfactant has been discussed. The results have shown that the CMC values decreased with an increase in the concentration of NaCl indicating that the Na + preferentially adsorbs onto the surface of the charged aggregate and facilitates the aggregate growth by suppressing the main impediment of electrostatic repulsion among head groups. Additionally, the values of Γ max are always higher in salt solutions as compared to those in pure water due to their salting out effect. The larger pC20 value indicates that the surfactant adsorbs more efficiently at the air/water interface and reduces surface tension more efficiently. In addition, the geminis in water show little or no break in their specific conductance versus surfactant molar concentration plots. This is attributable to protonation of the carboxylate group and strong Na + release during micellization.